Patient’s informed consent to treatment: legal and medical aspects – part II - Królikowska, Anna; Podciechowski, Lech; Hincz, Piotr; Wilczyński, Jan (Menopause Review/Przegląd Menopauzalny, 2011)
Obtaining the patient’s informed consent to an operating procedure and introduction of treatment is of fundamental importance both from a medical and legal point of view. Obtaining the patient’s legal informed consent to medical procedures is not often simple, though it is needed, cannot delay or limit the method of treatment. Experience shows that the patient’s informed consent is often obtained in a wrong and unlawful way and contrary to the legislator’s intention. The article is a review of legal norms currently in force